Year-Long Phenotypical Study of Calves Derived From Different Assisted-Reproduction Technologies - Lopes, Jordana S.; Soriano-Úbeda, Cristina; París-Oller, Evelyne; Navarro-Serna, Sergio; Canha-Gouveia, Analuce; Sarrias-Gil, Lucía; Cerón, José Joaquin; Coy, Pilar (Frontiers in Veterinary Science, 2022)
Assisted reproductive technologies play a major role in the cattle industry. An increase in the use of in vitro derived embryos is currently being seen around the globe. But the efficiency and quality of the in vitro derived embryo is substandard when compared to the in vivo production. Different protocols have been designed to overcome this issue, one of those being the use of reproductive fluids as supplementation to embryo culture media. In this study, in vitro derived calves produced with reproductive fluids added to their embryo production protocol were followed for the first year of life pairwise with their in vivo control, produced by artificial insemination, and their in vitro control, produced with standard supplementation in embryo production. The objective was to assess if any differences could be found in terms of growth and development as well as haematological and biochemical analytes between the different systems. All the analysed variables (physical, haematological and biochemical) were within physiological range and very similar between calves throughout the entire experiment. However, differences were more evident between calves derived from standard in vitro production and artificial insemination. We concluded that the use of reproductive fluids as a supplementation to the embryo culture media results in calves with closer growth and development patterns to those born by artificial insemination than the use of bovine serum albumin as supplementation.